The F-11 Sensory Neuron Model: A Scalable In Vitro Platform for Neuropathic Pain and Drug Screening - Nazwar, Tommy Alfandy; Laksono, Ristiawan Muji; Balafif, Farhad; Wardhana, Donny Wisnu; Balafif, Fachriy (Universitas Bio Scientia Internasional Indonesia, 2026)
Neuropathic pain remains a major therapeutic challenge, largely due to the translational disconnect between preclinical animal models and clinical efficacy in humans. This review critically evaluates the differentiated F-11 cell line, a hybridoma of mouse neuroblastoma and rat embryonic dorsal root ganglion (DRG) neurons, as a scalable, reproducible, and physiologically relevant in vitro platform for neuropathic pain research and analgesic drug screening. A detailed analysis of differentiation strategies highlights the critical interplay of neurotrophic factors (notably NGF), intracellular signaling modulators (such as cAMP elevators), and extracellular matrix cues in driving neuronal maturation. Functional validation via calcium imaging and electrophysiology confirms capsaicin responsiveness and action potential generation, mirroring native nociceptors. Its compatibility with medium-to-high-throughput screening and mechanistic studies including investigation of silent nociceptor sensitization in chronic pain conditions along with emerging applications in neuropathy models, makes it a valuable tool for de-risking drug candidates before animal studies.